The Effect of Strengthening Nurses' Clinical Roles on Service Quality in the Emergency Department - Frima Lestari Simanjuntak; Harif Fadhillah; Eni Widiastuti; Muhammad Hadi (GLOBAL HEALTH SCIENCE GROUP, 2026)
The Emergency Department (ED) is a service unit that requires nurses to possess strong clinical competencies to make rapid, accurate, and safe decisions. Strengthening nurses' clinical roles is an important factor in improving service quality, particularly in work environments characterized by high complexity and intense pressure. This study aimed to determine the effect of strengthening nurses' clinical roles on service quality in the Emergency Department of Awal Bros Panam Hospital (RSAB Panam). This study employed a quasi-experimental design with control and intervention groups. The study was conducted in the Emergency Department of RSAB Panam. The sample consisted of 32 emergency nurses who were divided into control and intervention groups, as well as patients receiving nursing care in the ED as respondents for service quality assessment. Total sampling was used for nurse participants. The intervention involved strengthening nurses' clinical roles based on Patricia Benner's theory through structured training, supervision, and clinical evaluationService quality was measured using the SERVQUAL instrument, which has demonstrated good validity (content and construct) and high reliability with Cronbach’s Alpha values >0.80. The data were analyzed using the Generalized Linear Model Repeated Measure. The results showed a significant effect of strengthening nurses' clinical roles on improving service quality in the ED. The Greenhouse–Geisser test indicated a p-value of 0.000, demonstrating a statistically significant change in service quality over time. The tests of between-subjects effects revealed a significant difference in service quality between the control and intervention groups with a p-value of 0.000. Improvements in service quality were more consistent in the intervention group compared to the control group. In conclusion, strengthening nurses' clinical roles has a significant effect on improving service quality in the Emergency Department.